Kajian Literatur Pembelajaran Multirepresentasi pada Materi Fisika Tingkat SMA (Universitas Negeri Surabaya, 2021)
Multi-representation ability is the ability to process a concept in other representations either verbally, diagrams, pictures, or mathematically. This study aims to determine the learning models and instruments developed in multi-representation research, the use of materials applied in multi-representation research, and the effectiveness of multi-representation learning. The method used is the literature study method with bibliometric analysis for journals or scientific articles that have been carried out and indexed by Scopus and Google Scholar. The data obtained through the software Publish or Perish as many as 20 journals in the form of metadata then complete the journal identity using Mendeley software. The metadata results were selected and analyzed using Vosviewer software to obtain a visualization map showing the relationship between the results. From the results of the analysis, it is known that the multi-representational learning models that are often applied are conceptual problem solving, guided inquiry, GIMuR, interactive conceptual, Problem Based Learning, and multi-representation learning. The types of assessment instruments used include essay tests, multiple-choice, Four Tier multiple-choice tests, mid-semester exams, and multi- representation worksheets. The materials that are often applied are newton's law, gravity newton law, straight motion, magnetism, work and energy. Multi-representation can facilitate students with different abilities and effectively improve student concepts understanding, critical thinking skills, and problem-solving. Keywords: Multi-representation, learning, physics